Unveiling the elusive: a case of missed hydrops fetalis - Tholu, Chandana Prasad; Ahmed, Iffat Wakeel; Dange, Shalini; Choudhary, Amruta Abhijit; Kamath, Anusha; Yadav, Anita (International Journal of Research in Medical Sciences, 2024)
Hydrops fetalis, characterized by abnormal fluid accumulation in fetal tissues, poses diagnostic challenges often leading to adverse outcomes. We present a case of a 26-year-old multigravida diagnosed with hydrops fetalis at 26 weeks, despite unremarkable antenatal visits. Detailed ultrasound revealed characteristic signs, prompting urgent intervention. Despite aggressive measures, the neonate succumbed shortly after birth. This case highlights the complexities of diagnosing and managing hydrops fetalis, emphasizing the need for heightened clinical awareness. Diagnostic steps, including fetal ultrasound and genetic testing, are pivotal for confirming diagnosis and guiding management, underlining the critical role of comprehensive prenatal care in improving outcomes.